Those who can don't want to, and those who want to can't: An eco-evolutionary mechanism of soil carbon persistence. (November 2022) - Bonner, Mark TL.; Franklin, Oskar; Hasegawa, Shun; Näsholm, Torgny
Abstract: Reliable manipulation of soil organic matter (SOM) – a necessity for optimal land management – is constrained by our limited mechanistic understanding of SOM formation. Here we propose a novel mechanistic element that may contribute to SOM dynamics, supplementing existing frameworks, based on evolutionary-ecological rather than chemical or physical limitations to decomposition. We argue that decomposition of some substrates may be constrained by spatial competition from opportunists. We describe and test a mathematical model based on our framework, providing a proof-of-concept that substrate can, in principle, be spared decomposition and accumulate even when it is physically and chemically accessible. Our framework can help explain a variety of SOM dynamics, including priming and the suppression of decomposition by nitrogen addition, as well as the typical composition of SOM. An augmented mechanistic framework for understanding SOM dynamics can help guide targeted empirical study, which in turn can contribute to more optimised land management. Highlights: Physically accessible soil organic carbon may be ecologically protected. We model competition between opportunists and oxidisers. Non-hydrolysable low C:N substrate is predicted to remain undecomposed.